Comparative Phylogenomic Analysis of Escherichia coli ST131 Isolates and IncF-type Plasmids from North Carolina Community Hospitals and Other Regions of the United States. (4th October 2017) - Kanamori, Hajime; Johnson, Timothy; Parobek, Christian; Juliano, Jonathan; Johnson, James R; Johnston, Brian D; Weber, David J; Rutala, William A; Anderson, Deverick
Abstract: Background: Escherichia coli sequence type 131 (ST131), associated with CTX-M-15-type extended-spectrum β-lactamases (ESBLs), predominates globally among multidrug-resistant (MDR) E. coli . Among MDR E. coli ST131 isolates from North Carolina and other US regions, we explored genetic associations of the H 30Rx and H 30R1 subclones with IncF-type plasmid variants. Methods: Sequence data from 144 clinical E. coli isolates, including 39 MDR ST131 isolates from our 7 NC community hospitals and previous 104 ST131 isolates from other US regions, were analyzed and compared. Specific genes were sought using a bioinformatic pipeline at the Center for Genomic Epidemiology and BLAST. Evolutionary analyses were performed using MEGA7. Plasmid incompatibility groups and its STs were identified using PlasmidFinder and pMLST. Comparisons of the completed sequences of 2 ST131 reference plasmids with 144 ST131 draft genome assemblies were performed using CGView Comparison Tool, and circular comparison maps were generated. Among 31 bla CTX-M -containing contigs, bla CTX-M gene insertion sites were examined. Results: In the core genome phylogeny, the H 30R1 and H 30Rx clades were placed within a larger H 30R clade (Figure 1). pMLST revealed association of IncF[F2:A1:B-] plasmids (mostly bla CTX-M-15 -positive) with H 30Rx, and IncF[F1:A2:B20] plasmids (all bla CTX-M-15 -negative) with H 30R1. The ST131-associated IncF[F2:A1:B-] plasmids from NC generally resembled those from other US regions (Figure 2). However, in contrast to the others, some of the NC plasmids lacked regions previously described as gisland 1 h and/or the gColla-region, h in addition to gisland 2 h (Figure 3). Among the 31 NC ST131 isolates producing CTX-M (26 H 30Rx and 5 H 30R1 isolates), bla CTX-M-15 was inserted at the same chromosomal site in 3 H 30Rx isolates, at different chromosomal sites in 3 H 30Rx isolates, and on IncF plasmids in 1 H 30Rx and 1 H 30R1 isolates, suggesting that the bla CTX-M -containing gene cassette has moved around among and/or within these strains. Conclusion: Our genomic and plasmid analysis of community hospital-source ST131 isolates demonstrated fixation and ongoing evolution of specific plasmids within the separate but closely related H 30Rx and H 30R1 sublineages. Disclosures: J. R. Johnson, Crucell/Janssen: Consultant, Consulting fee Merck: Grant Investigator, Grant recipient Tetraphase: Grant Investigator, Research grant Actavis/Allergan: Grant Investigator, Grant recipient